ظاهرة إختطاف الأطفال من وجهة نظر وسائل الإعلام التلفزيون أنموذجا - عطية، عفاف (جامعة الوادي university of Eloued, 2017)
Abstract: The aim of this study is to try to identify the phenomenon of child abduction from the point of view of the media. A major question was asked: How did the local media address the abduction of children in Algeria? -It included a number of sub-questions: -Is the method of subtraction phenomenon of abduction of children through different media quotas reflect all issues of the problem? -Is the content of the media message in different sections gave a clear picture of the phenomenon of child abduction? Based on the content analysis methodology for a 90-minute news share, and on a sample of 10 households in the Valley area, the analysis of content and interview was adopted. The study reached a number of results, including: 1We conclude that the highest percentage of the 90-minute news coverage of the images related to the incident is the picture of the victims, at 26.82%. 2We conclude that the highest percentage of the source of information provided in the 90-minute news coverage is Al-Nahar TV correspondents, which reached 57.14%. 3We conclude that the highest percentage of the subject category and percentage in the daytime channel is the losses resulting from the kidnapping and 15.3%. 4We conclude that the highest percentage of losses resulting from the abduction of children in the 90-minute news share is the death rate of 81.81%.
دراسة تحليل المضمون لحصة 90 دقيقة على قناة النهار
مذكرة ماستر في العلوم الاجتماعية تخصص علم اجتماع الاتصال
Keywords: إختطاف الأطفال، التلفزيون; Enlèvement d'enfants, télévision; Child abduction, TV